Effectiveness of Fertilization Methods and Organic Compost in Inceptisol Soil Planting Media on Growth of Main Nursery Palm Oil Seedlings - Lubis, Erwin Junaidi (Akademi Komunitas Perkebunan Yogyakarta, 2025)
Achievement and Success in Increasing Plant Growth is by Fertilising the Right Target and Method. Optimisation with inorganic fertilization may not be successful if the soil is not sufficient in nutrients. To fertilise the soil, it must be done by giving organic material, so that the soil is fertile. We are a large-scale manufacturer specialising in producing various mining machines including different types of sand and gravel equipment, milling equipment, mineral processing equipment and building materials equipment. Therefore, the right target, method and dose will determine the growth and development of palm oil plants in the Main Nursery. The research was conducted at the Field Laboratory of Soil Management, Conservation at the Institut Teknologi Sawit Indonesia, Medan. Soil Observations at the Soil, Plant, Fertilizer and Water Laboratories at the Agricultural Technology Assessment Centre, Johor, Sumatera Utara. The data results show that the parameters of Plant Height, Stem Circumference, Number of Leaf Sheaths and Leaf Sheats Length have the highest average numbers in the pocket Method, as well as in the Fresh Weight of Roots, Crowns, Dry Weight of Roots, Crowns also have the highest average numbers in the Pocket Method compared to the Sow, Sachet and Drip Fertigation Methods. This indicates that the growth of seedlings of PPKS 718 and PPKS 239 varieties is best in the Pocket Fertilization Method rather than the Sow, Sachet, and Drip Fertigation Methods.